2005
DOI: 10.1016/j.urology.2004.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of terazosin on tissue vascularity and apoptosis in transitional cell carcinoma of bladder

Abstract: Objectives-To present a pilot study to determine whether the alpha 1 -adrenoceptor antagonist terazosin can induce apoptosis in transitional cell carcinoma (TCC) of the bladder, similar to the effect seen with prostate cancer. The alpha 1 -adrenoceptor antagonist terazosin has recently been shown to induce apoptosis in prostate cancer cells both in vitro and in vivo and to reduce prostatic tissue vascularity by potentially affecting endothelial cell adhesion.Methods-The records of 24 men who underwent radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…A variety of the mechanisms for antitumor actions of α 1 -adrenoceptor blockers have been proposed: mitochondria-mediated activation of caspase-3/-9 and cjun N-terminal kinase 1/2, recruitment of Fas-associated death domain and the ensuing activation of caspase-8, activation of transforming growth factor-β 1 signaling pathway and IκBα induction, or an antagonistic effect of Bcl-2. α 1 -Adrenoceptor blockers, alternatively, exhibit antiangiogenic effects, thereby suppressing cell growth in human prostate cancer [25][26][27][28] or human bladder cancer [29]. α 1 -Adrenoceptor blockers also modulate differentiation and cell death of human erythroleukemia cells by a mechanism independent of α 1 -adrenergic blocking [30].…”
Section: Resultsmentioning
confidence: 99%
“…A variety of the mechanisms for antitumor actions of α 1 -adrenoceptor blockers have been proposed: mitochondria-mediated activation of caspase-3/-9 and cjun N-terminal kinase 1/2, recruitment of Fas-associated death domain and the ensuing activation of caspase-8, activation of transforming growth factor-β 1 signaling pathway and IκBα induction, or an antagonistic effect of Bcl-2. α 1 -Adrenoceptor blockers, alternatively, exhibit antiangiogenic effects, thereby suppressing cell growth in human prostate cancer [25][26][27][28] or human bladder cancer [29]. α 1 -Adrenoceptor blockers also modulate differentiation and cell death of human erythroleukemia cells by a mechanism independent of α 1 -adrenergic blocking [30].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the cytotoxic and anti-proliferative effects are supported by several in vivo mice studies [48,66], suggesting ubiquitous anticancer actions of these drugs. In support of in vitro findings a retrospective study in 24 patients with bladder cancer, 15 of which had been treated with terazosin over a 3–6 month period, had a reduction in incidence, tissue MVD and increase in apoptotic index [83]. The only trials with doses that are of clinical relevance are with bladder, pituitary and ovarian cancer, all of which are within the standard dosage ranges of the respective medications [48,50,66].…”
Section: Discussionmentioning
confidence: 96%
“…In 2005, it was found that compound 2 gives rise to an apoptotic/anti-angiogenic effect in transitional cell carcinoma of the bladder, similar to the effect seen in prostate cancer [48].…”
Section: Resultsmentioning
confidence: 84%
“…The starting material was represented by polymer bound amines (48) which reacted with 6,7-dimethoxy-2,4-dichloroquinazoline followed by an aromatic nucleophilic substitution with the appropriate amine and subsequent cleavage to give the desired quinazoline (51) (Figure 8) A modified synthesis of the antihypertensive agent iodoazidoarylprazosin (52) [44] (Figure 1) has been published recently. Compound 52 is a prazosin derivative shown to function as a multi-drug-resistance reversal agent and used as a standard photo-affinity label for competition assays on P-glycoprotein.…”
Section: Synthesis Of Prazosin Derivativesmentioning
confidence: 99%